Check GMAT Club Decision Tracker for the Latest School Decision Releases https://gmatclub.com/AppTrack

 It is currently 24 May 2017, 05:21

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

Problem

Author Message
Intern
Joined: 07 Mar 2006
Posts: 6
Followers: 0

Kudos [?]: 0 [0], given: 0

Show Tags

19 Mar 2006, 12:27
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Value of X?

2^(x+4) = 4*(6^(2x+4)

Any idea how to solve this?[/quote]
Manager
Joined: 20 Mar 2005
Posts: 201
Location: Colombia, South America
Followers: 1

Kudos [?]: 16 [0], given: 0

Show Tags

19 Mar 2006, 13:48
rdangol wrote:
Value of X?

2^(x+4) = 4*(6^(2x+4)

Any idea how to solve this?
[/quote]

In real gmat you would probably use backsolving

for this one:

2^(x+4) / 4 = 6^(2x+4)

2^(x+4) / 2^2 so

2 ^ (x+2) = 6^(2x+4)

2^x * 4 = 6^2x * 6^4

2^x = 36^x * 1296/4

1 / 324 = 36^x / 2^x

1 / 324 = (36 / 2 ) ^ x

1 / 324 = 18 ^ x

and 324 is 18^2

so x = -2
VP
Joined: 29 Dec 2005
Posts: 1343
Followers: 10

Kudos [?]: 62 [0], given: 0

Show Tags

19 Mar 2006, 15:17
conocieur wrote:
rdangol wrote:
Value of X?

2^(x+4) = 4*(6^(2x+4)

Any idea how to solve this?
In real gmat you would probably use backsolving. for this one:

2^(x+4) / 4 = 6^(2x+4)
2^(x+4) / 2^2 so
2 ^ (x+2) = 6^(2x+4)
2^x * 4 = 6^2x * 6^4
2^x = 36^x * 1296/4
1 / 324 = 36^x / 2^x
1 / 324 = (36 / 2 ) ^ x
1 / 324 = 18 ^ x
and 324 is 18^2
so x = -2

undoubtly wonderful.
Senior Manager
Joined: 29 Jun 2005
Posts: 403
Followers: 2

Kudos [?]: 21 [0], given: 0

Show Tags

20 Mar 2006, 12:29
Hi,

It can be solved much easier:
2^(x+2)=36^(x+2)
2is not equal to 36, thus x+2=0 x=-2
Manager
Joined: 20 Mar 2005
Posts: 201
Location: Colombia, South America
Followers: 1

Kudos [?]: 16 [0], given: 0

Show Tags

20 Mar 2006, 13:13
Dilshod wrote:
Hi,

It can be solved much easier:
2^(x+2)=36^(x+2)
2is not equal to 36, thus x+2=0 x=-2

yes, I like your approach way better
20 Mar 2006, 13:13
Display posts from previous: Sort by